Critical Accounting: A Bibliometric and Systematic Review - Yohanes Halan (Universitas Katolik Darma Cendika, 2026)
Critical Accounting has emerged as a paradigm that fundamentally redefines the perceived neutrality of accounting in the context of social power relations. In light of its proliferation, it is imperative to conduct a thorough and contemporary analysis of its evolution and prevailing trends to fully comprehend its current trajectory. The primary aim of this study is to assess the ongoing relevance of Critical Accounting scholarship, delineate the global dispersion of academic inquiries, and elucidate nascent theoretical and practical implications. A systematic literature review was undertaken in accordance with the PRISMA guidelines, supplemented by bibliometric analysis. Data were extracted from the Scopus database as of March 15, 2026, and subsequently analyzed utilizing VOSviewer software to illustrate intellectual networks and thematic clusters. The results indicate a significant escalation in publication output since the 1990s, culminating in a zenith during the mid-2020s, with a notable shift in emphasis towards decolonization, artificial intelligence, and digital exploitation. The geographical distribution of research remains predominantly concentrated in the UK, Australia, and the USA, with the journal Critical Perspectives on Accounting functioning as the principal intellectual nexus. This study substantiates that Critical Accounting continues to be an essential domain for prospective academic exploration. The findings suggest a transformation towards a more emancipatory discipline, repositioning accounting from a mere passive documentation tool to a proactive instrument for social justice and the public good.